Validitas Soal Berbasis HOTS Berbantuan Quizizz untuk Melatih Kemampuan Berpikir Kritis pada Materi Sistem Pencernaan - Yusuf, Sabrina; Dama, Lilan; Usman, Nurul Fajryani; Yusuf, Frida Maryati; Akbar, Muh. Nur (Biocaster : Jurnal Kajian Biologi, 2025)
Critical thinking skills are one of the abilities needed by students to face the challenges of the 21st century. This study aims to describe the validity of Higher Order Thinking Skills (HOTS)-based questions developed to train students' critical thinking skills. This research used a developmental research model (ADDIE) model. The parameter measured was the product's validity level, consisting of HOTS-based questions, using a validation instrument involving two validators: a material expert and a learning device expert. The subjects in this study were 11th-grade high school students. The questions were developed in essay format and presented through the digital platform Quizizz as a learning evaluation medium. The validation results showed that the questions fell into the appropriate to very appropriate category, with a percentage range of 62.50% - 81.25% for the material aspect, and 81.25% - 100% for the learning device aspect. Thus, the developed HOTS-based questions are deemed appropriate for use in learning evaluation activities and have the potential to support the development of students' critical thinking skills.